INCIDENCIA DEL GASTO PÚBLICO Y LAS EXPORTACIONES EN EL CRECIMIENTO ECONÓMICO EN ECUADOR: UN ANÁLISIS DE CAUSALIDAD Y COINTEGRACIÓN, PERÍODO 1970-2017 - Ordóñez Lara, María Paula (2019)
The objective of this research is to analyze the incidence of public spending and exports on economic growth in Ecuador during the period 1970-2017. The study is based on the Keynesian hypothesis (1936) that states that public spending is an exogenous factor that influences economic growth and can be used as a political instrument and the Export Led Growth (ELG) hypothesis where economic growth is driven for exports. Using data from time series obtained from the Central Bank of Ecuador (2017) and econometric estimates of cointegration and causality. It is concluded that Ecuador has a positive short and long term correlation between the study variables. In addition, the causality test of Granger (1969) demonstrated the importance of exports in public spending and in the Ecuadorian economy. These results coincide with those obtained in the studies carried out by Comín, Fuentes and López (2009) and Rodríguez Benavides and Venegas-Martínez (2011). A possible economic policy would be aimed at the efficient management of economic resources by the government, increasing public spending on the infrastructure and equipment of economic sectors, in order to boost domestic production and increase exports that are the engine of income in Ecuador.